Islamic Republic of Iran : Staff Report for the 2002 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2002)
This 2002 Article IV Consultation for the Islamic Republic of Iran states that the overall macroeconomic developments in 2001/02 were marked by sustained economic activity in the non-oil sector, improved fiscal and external positions, and declining inflation trends. Against a background of improved business confidence, the authorities continued to implement economic reforms in line with their Third Five-Year Development Plan. They also successfully issued a Euro 625 million Eurobond, marking Iran's return to international financial markets.